2021
DOI: 10.3389/fcell.2020.623948
|View full text |Cite
|
Sign up to set email alerts
|

TET-Mediated Epigenetic Regulation in Immune Cell Development and Disease

Abstract: TET proteins oxidize 5-methylcytosine (5mC) to 5-hydroxymethylcytosine (5hmC) and further oxidation products in DNA. The oxidized methylcytosines (oxi-mCs) facilitate DNA demethylation and are also novel epigenetic marks. TET loss-of-function is strongly associated with cancer; TET2 loss-of-function mutations are frequently observed in hematological malignancies that are resistant to conventional therapies. Importantly, TET proteins govern cell fate decisions during development of various cell types by activat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 160 publications
(234 reference statements)
2
30
0
Order By: Relevance
“…Additionally, many small molecules including circular RNAs and methylation modifiers (such as N6-methyladenosine and 5-hydroxymethylcytosine) have not been examined in dNK cells. Whether the RNA modifications [ 84 , 85 ] in dNK cells and pNK cells regulate biological immune functions during pregnancy is worth exploring in the future.…”
Section: Future Directionsmentioning
confidence: 99%
“…Additionally, many small molecules including circular RNAs and methylation modifiers (such as N6-methyladenosine and 5-hydroxymethylcytosine) have not been examined in dNK cells. Whether the RNA modifications [ 84 , 85 ] in dNK cells and pNK cells regulate biological immune functions during pregnancy is worth exploring in the future.…”
Section: Future Directionsmentioning
confidence: 99%
“…The second route is achieved through the actions of a set of proteins (Ten-Eleven-Translocation (TET) family) that further modify the methylgroup on CpG motifs. (Tsiouplis et al, 2020).…”
Section: Enzymes That Regulate Dna Methylationmentioning
confidence: 99%
“…3. A set of 'eraser' enzymes work in effective opposition to the DNA methyl transferases, by modifying the methylation mark (Tsiouplis et al, 2020). 4.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to being an general antioxidant, VC has an unique property to reduce Fe(III) to Fe(II) for epigenetic enzymes, including Ten-Eleven Translocation (TET). family proteins (TET1, TET2, TET3) are essential for DNA demethylation by oxidizing 5-methylcytosine (5mC) to mainly 5-hydroxymethylcytosine (5hmC) 39,40,52 . Previous studies have shown that TET2 and TET3 are required for B cell development and function [53][54][55][56][57][58][59] .…”
Section: The Effect Of Vc Is Dependent On Either Tet2 or Tet3mentioning
confidence: 99%
“…TET enzymes oxidize 5mC into oxidized bases including 5hmC, a stable epigenetic medication and an intermediate for DNA demethylation 40,52,60 . To confirm VC indeed enhances TET activity, we used DNA dot blot to semi-quantitatively measure the level of 5hmC in B cells.…”
Section: Vc Remodels the Genome-wide 5hmc Modificationmentioning
confidence: 99%